2019
DOI: 10.1177/1744259119891753
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal assessment of north-facing, cold attic spaces under the eaves with varying structural roof scenarios

Abstract: The objective of this study was to test whether compliance with the current Danish best practice recommendations concerning design of the cold attic space will prevent damaging moisture levels. The project was performed as a full-scale experimental setup in the cool temperate climate of Denmark. The setup comprised 18 north-facing attic spaces with varying ventilation principles and varying infiltration scenarios. The relative humidity and temperature were measured in attic spaces, indoor and outdoor, for almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…During the phase with the 70-mm XPS on the roof, the cavity temperature remained 0°C-1°C above outdoor air. After closing of the ventilation inlet, the cavity temperatures rose to 1°C-2°C above outdoor air on average, which corresponds to the temperature increase obtained by Jensen et al (2020) in an unventilated roof cavity with 50-mm-thick exterior polystyrene insulation. The outdoor temperature increased 4 days later, and the cavity temperature excesses decreased to zero.…”
Section: Results From the Experimental Studiesmentioning
confidence: 60%
See 2 more Smart Citations
“…During the phase with the 70-mm XPS on the roof, the cavity temperature remained 0°C-1°C above outdoor air. After closing of the ventilation inlet, the cavity temperatures rose to 1°C-2°C above outdoor air on average, which corresponds to the temperature increase obtained by Jensen et al (2020) in an unventilated roof cavity with 50-mm-thick exterior polystyrene insulation. The outdoor temperature increased 4 days later, and the cavity temperature excesses decreased to zero.…”
Section: Results From the Experimental Studiesmentioning
confidence: 60%
“…In the study, the lowest attic RH during the cold season was achieved with the additional insulation. The experiments by Jensen et al (2020) showed that exterior insulation increased temperatures in an unventilated roof cavity, but the mold risk remained similar to the case without external insulation. It seems that increase of the exterior thermal resistance (R value) may improve cavity conditions in HI structures, but finding an optimal ventilation rate is challenging.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The airtightness of the ceiling prevents both convection of moist air from the dwelling, but also reduces the possibility of downward airflow of possibly contaminated air. A recent Danish study of small cold attic spaces under the eaves stressed the importance of an airtight ceiling, as ventilation is not always sufficient for removal of moist air [21]. A Swedish study [1] also determined the side effect of mould odour in the dwelling due to mould growth in the attic.…”
Section: Consequences Of Moisture and Air Exchangementioning
confidence: 99%
“…Note that some measurements from house 22 exhibit excess moisture up to 16 g/m 3 in single measurements. Top: houses with vapour barriers(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), bottom: houses without vapour barriers(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%